FEATURES OF SURGICAL DENTISTRY INTERMEDIATE MEDICINE TEACHING AT THE POST-GRADUATE EDUCATION DEPARTMENT FOR DOCTORS OF UKRAINIAN MEDICAL STOMATOLOGICAL ACADEMY - O.V. Gurzhiy; S.V. Kolomiiets; V.L. Melnik; O.E. Berezhna (Український стоматологічний альманах)
Improvement of teaching methods, search for new forms of active cognitive practice education for internship-doctors are important tasks of improving the quality of specialists training in the system of post-graduate education.